Audit Fees as Moderation of the Influence of Code of Ethics, Audit Tenure and Public Accounting Firm Rotation on Audit Quality in the Perception of External Auditors - Leni Maulina; Adam Zakaria; Achmad Fauzi (PT FORMOSA CENDEKIA GLOBAL, 2025)
With audit fees acting as a moderating variable, this study attempts to investigate the effects of the code of ethics, audit tenure, and audit firm rotation on audit quality. Using WarpPLS 8.0 software and the Partial Least Squares technique, a quantitative approach was adopted. Participants in a professional training program run by the Indonesian Institute of Certified Public Accountants (IAPI) were auditors or public accountants. 131 respondents were given questionnaires to complete during the session in order to collect data. The findings show that audit quality is positively but statistically insignificantly impacted by the audit fee, audit tenure, and code of ethics. On the other hand, audit quality is positively and significantly impacted by the rotation of public accounting firms. Additionally, there is no discernible moderating effect of audit fees on the association between audit quality and the code of ethics, audit tenure, or firm rotation. According to these results, even if the factors are directionally favorable, their influence is insufficient to significantly improve audit quality within the parameters of this study